1992
DOI: 10.1002/ana.410310402
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine expression in the brain during the acquired immunodeficiency syndrome

Abstract: The pathogenesis of central nervous system (CNS) disease in acquired immunodeficiency syndrome (AIDS) is poorly understood but may be related to specific effects of the immune system. Cytokines such as tumor necrosis factor and interleukin-1 may have toxic effects on CNS cells and have been postulated to contribute to the pathogenesis of the neurological complications of human immunodeficiency virus (HIV) infection. To characterize viral and immunological activity in the CNS, frozen specimens taken at autopsy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
262
0
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 562 publications
(270 citation statements)
references
References 57 publications
7
262
0
1
Order By: Relevance
“…As alluded to previously, TNF-␣ and IL-1␤ are elevated in the brain, spinal cord, and cerebrospinal fluid of AIDS patients (47,48). Importantly, the amount of TNF-␣ present in brain parenchyma at postmortem appears to correlate with the degree of dementia determined preagonally (47). Our findings suggest therefore that at least one pathway for the neuronal injury observed in HAD may be cytokine-induced release of macrophage toxins such as cysteine.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…As alluded to previously, TNF-␣ and IL-1␤ are elevated in the brain, spinal cord, and cerebrospinal fluid of AIDS patients (47,48). Importantly, the amount of TNF-␣ present in brain parenchyma at postmortem appears to correlate with the degree of dementia determined preagonally (47). Our findings suggest therefore that at least one pathway for the neuronal injury observed in HAD may be cytokine-induced release of macrophage toxins such as cysteine.…”
Section: Discussionsupporting
confidence: 74%
“…In fact, previous studies have shown that gp120 stimulates the secretion of both TNF-␣ and IL-1␤ by human monocytic cells (26,27). As alluded to previously, TNF-␣ and IL-1␤ are elevated in the brain, spinal cord, and cerebrospinal fluid of AIDS patients (47,48). Importantly, the amount of TNF-␣ present in brain parenchyma at postmortem appears to correlate with the degree of dementia determined preagonally (47).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…For example, activation of microglia and diffuse microgliosis were previously shown to correlate with ventricular expansion and neuropathological changes in HAD. 15,46,47 The discordance, in select patients, between the level of pathology and the clinical course of disease may be related to several factors. These include genetic susceptibilities to dementia in patient subpopulations, peripheral immune activation, and limitations of autopsy tissue analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Viral particles, however, are not the only mediators of CNS dysfunction and neuron toxicity. HIV-induced encephalitis is associated with immune activation of glial cells that results in alterations of normal cell biology, notably secretory functions (41)(42)(43)(44)(45). Improper regulation of these factors can lead to impaired cellular functioning, modified neurotransmitter action, amplified inflammation and neuronal damage.…”
Section: Macrophage Driven Pathogenesismentioning
confidence: 99%